Variations of the Physicochemical Parameters and Metal Levels and Their Risk Assessment in Urbanized Bagmati River, Kathmandu, Nepal. (30th November 2016) - Paudyal, Rukumesh; Kang, Shichang; Sharma, Chhatra Mani; Tripathee, Lekhendra; Sillanpää, Mika
Abstract : During post-monsoon 2013, surface water samples were collected form 34 sites from the Bagmati River and its tributaries within the Kathmandu Valley to assess the river water quality. The physical parameters were measured on site and major ions (Na +, N H 4 +, K +, Mg 2+, Ca 2+, Cl −, S O 4 2 -, andN O 3 - ) and 17 elements in water were analyzed in the laboratory. Conductivity ranged from 21.92 to 846 μ S/cm, while turbidity ranged from 2.52 to 223 NTU and dissolved oxygen (DO) ranged from 0.04 to 8.98 mg/L. The ionic and elemental concentrations were higher in the lower section where the population density is high compared to the headwaters. The large input of wastewater and organic load created anoxic condition by consuming dissolved oxygen along the lower belt of the river. The concentration of the elements was found to be in the order of Mn > Zn > Ti > Rb > Cr > Cu > Sc > Ni > V > Li > Co > Mo > Cd > Y > Ga > Be > Nb. The concentration of Mn, Cd, Cr, Co, and Zn was particularly higher in urban and semiurban sections. Enrichment factor (EF) calculations for Cd, Co, and Zn showed their highly enriched values indicating that these elements originated from anthropogenic sources. Preliminary risk assessments were determined by the hazard quotient (HQ) calculations in order to evaluate the health risk of the metals. TheH Q i n g e s t i o n values of elements were found to be in the order Sb > Mn > Cr > V > Co > Cd > Cu > Zn > Ni > Li > Mo with all averaged HQ values less than 1, indicating no or limited health risk of metals from the river to the local residence. However the values of Sb in some parts of the Bagmati were close to unity indicating its possible threat. Anthropogenic activities like industrial activities, municipal waste water, and road construction besides the river appear to control the chemical constituent of the river water. Overall the river was highly polluted with elevated concentrations of major ions and elements and there is a need for restoration projects.